Assessment of broadcast media coverage of climate change in Kenya - Juma, Angela Paucia; Maina, Jane; Wabwire, Jonai (Journal of New Media and Mass Communication, 2025)
Climate change continues to pose significant environmental and socio-economic challenges worldwide, making effective communication essential for raising public awareness and encouraging action. This study aims to examine the coverage of climate change by Radio Lake Victoria and assess its influence on community perceptions and responses. A descriptive survey design was employed, utilizing a mixed-methods approach that combined qualitative in-depth interviews with quantitative questionnaires. Probability sampling was used to select 396 households in Nyando Sub-County, while a census approach targeted 20 members of the radio station’s editorial team. The study reveals that Radio Lake Victoria provides coverage on climate change, with particular emphasis on environmental impacts and potential solutions. However, the reporting is limited in depth regarding underlying causes, long-term effects, and practical guidance on sustainable adaptation and mitigation strategies. The findings highlight the need for more analytical, contextualized, and solution-oriented climate reporting. These insights are valuable to journalists seeking to refine editorial approaches, policymakers developing climate communication strategies, and researchers aiming to advance knowledge on grassroots climate change communication and community resilience.